Fragilité du géocyberespace à l’heure des conflits cybernétiques - Henry Bakis (Netcom)
While acts of cyber hostility are increasing around the world, the cyber armaments race continues. This highlights the vulnerability of ICT in every dimension. Despite the urgency of the problem, effective control of Internet security poses real challenges (political, legal and technical). This note is an introduction to the following paper (Roche & Blaine) which calls for the signing of an international convention on cyber disarmament.